A bedside ultrasound technique for fluid therapy monitoring in severe hypovolemia: Tissue Doppler imaging of the right ventricle - Unluer, Erden Erol (Interv Med Appl Sci, 2017)
Fluid therapy is one of the main issues for hemodynamic resuscitation. Tissue Doppler imaging (TDI) of the right ventricle (RV) with bedside ultrasound (BUS) technique is a new dynamic method to identify fluid responsiveness in patients with hypotension. Here, we present the case of a hypotensive patient monitored with TDI measurements of RV. A 75-year-old male patient was admitted to the emergency department (ED) with the complaint of diarrhea. He was in severe hypovolemia, with hypotension, tachycardia, and tachypnea. His laboratory results were normal. BUS was performed on the patient by the ED physician. The velocity of the excursion of the tricuspid valve measured at presentation was 14.47 cm/s and, together with collapsed inferior vena cava (IVC), this finding led to the decision to begin fluid therapy immediately. The patient underwent 2 L of fluid therapy with 0.9% NaCl in a 2-h period. Control BUS after fluid therapy revealed decreased TDI velocity of tricuspid annulus to 11.81 cm/s and dilated IVC not collapsing sufficiently with respiration. The patient received his maintenance therapy after admission to the internal medicine department and was discharged from the service after 3 days. TDI in fluid responsiveness may find a clinical role in the future by the clinical studies.